Motivasi dan Harapan Kembali Para Foreign Terrorist Fighter dari Suriah ke Indonesia - Dhio Kusuma Putra; Adrianus Eliasta Meliala (Cakrawala Repositori IMWI, 2023)
This research aims to explore the motivations and expectations of Indonesian Foreign Terrorist Fighters to return to their home countries. The development of this research uses a qualitative approach through interviews with resource persons and literature studies from related literature. Furthermore, the data obtained was analyzed using the Miles and Huberman analysis technique. The results of this study show that there are four factors of encouragement or motivation and three hopes of returning from the Foreign Terrorist Fighter, including continuing jihad, regret, disappointment, and the desire to survive. While the return expectations of the Foreign Terrorist Fighter, namely global jihad, normal life, and decent life.